Elastic and Electrical Properties Analysis of Sedimentary Rocks in Southern of Semanggol Formation - bin Khalil, Mohammad Zakwan Khair (Universiti Teknologi PETRONAS, 2015)
This project is about studying the elastic and electrical properties of sedimentary rocks found in Gunung Semanggol. The study area is mostly made up of interbedded between sandstone and shale. Bukit Merah area is added to this study to enhance the understanding of rock physics properties in southern of Semanggol Formation. The accompanied objectives are to investigate the sandstone reservoir potential and to evaluate the environment setting in Gunung Semanggol and Bukit Merah. The scope of this research is divided into two phase. In first phase, this research will provide geological study by collecting data and sample of the area, investigate structural and clastic features of selected outcrop and describe mineral composition of the outcrop. Then, a geological map of the study area will be provided and updated. From petrographic studies, it is found that sandstone in Gunung Semanggol is fine to medium grain with moderately sorted while sandstone in Bukit Merah made up of medium to coarse grain with poor of grain sorting. Second phase of this research is focusing on laboratory work to measure and determine elastic and electrical properties of samples collected in Gunung Semanggol. Physical measurement and calculation are used to describe properties of the rock. Geophysical study of the area will be conducted by analyzing the rock physics properties such as Vp/Vs ratio, Poisson’s ratio, bulk modulus, young’s modulus and others. Electrical properties is done through resistivity analysis.